Ultraviolet-proof heat-insulating film and preparation method thereof

By loading M-phase vanadium dioxide and copper sulfide on carbon nanotubes and combining with nanocore-shell zinc oxide, an insulation film with excellent ultraviolet and near-infrared barrier properties was prepared, which solved the poor effect of the existing thermal insulation film. and the problem of high cost, more efficient thermal insulation effect and lower production costs are achieved.

CN119391019APending Publication Date: 2025-02-07JIANGSU YAOSHENG NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411676931.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing thermal insulation films are not effective in blocking ultraviolet and infrared rays, and at the same time, they are costly and need improvement.

Method used

By loading M-phase vanadium dioxide and copper sulfide on carbon nanotubes and combining with nanocore-shell zinc oxide, a heat insulation film with excellent ultraviolet and near-infrared barrier properties was prepared.

Benefits of technology

It significantly improves the ultraviolet barrier and thermal insulation properties of the thermal insulation film, while reducing production costs and extending service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005147262110000101
    Figure BDA0005147262110000101
Patent Text Reader

Abstract

The invention discloses an anti-ultraviolet heat-insulating film and a preparation method thereof, and belongs to the technical field of heat-insulating films, and the preparation method comprises the following steps: S1, ultrasonically dispersing M-phase-loaded vanadium dioxide carbon nanotubes in a copper sulfate pentahydrate aqueous solution, then adding a sodium thiosulfate aqueous solution, reacting at 90 DEG C for 1 hour, filtering and drying to obtain hybrid modified carbon nanotubes; s2, ultrasonically dispersing the hybrid modified carbon nanotubes and nano core-shell zinc oxide in deionized water, then adding polyvinyl alcohol, stirring and mixing at 90-95 DEG C for 2 hours to obtain a membrane casting solution, then blade-coating a glass plate with the membrane casting solution, and drying to obtain the ultraviolet-proof heat-insulating membrane; according to the invention, a small amount of hybrid modified carbon nanotubes and nano core-shell zinc oxide are added into polyvinyl alcohol, so that the prepared heat-insulating film has excellent barrier properties to ultraviolet rays and near infrared rays at the same time, thereby bringing a remarkable heat-insulating effect and having a wide application space.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermal insulation films, and in particular relates to an anti-ultraviolet thermal insulation film and a preparation method thereof. Background Art

[0002] In the hot summer, sunlight passes through the car glass and raises the temperature inside the car, which not only affects the comfort and skin health of the drivers and passengers, but also accelerates the aging of the car's interior materials, and also increases the car's air conditioning load and fuel consumption. Sunlight is composed of ultraviolet rays, visible light and infrared rays. The wavelength of ultraviolet rays is generally between 280-400nm, the wavelength of visible light is generally between 380-780nm, and the wavelength of infrared rays is generally between 700-2400nm. Ultraviolet rays account for 3%, visible light accounts for 44%, and far and near infrared rays account for 53% of the composition of sunlight. Thermal insulation film can reduce the impact of solar radiation on drivers and passengers by blocking a large amount of infrared and ultraviolet light, effectively improve the temperature inside the car, reduce the burden of air conditioning, and achieve energy-saving and environmental protection effects; it also reduces glass splashing when the glass is broken and improves safety performance.

[0003] However, the existing thermal insulation films still have shortcomings such as low visible light transmittance, poor infrared and ultraviolet shielding effect, and high production cost. It is necessary to further improve the existing thermal insulation films and their preparation methods. Summary of the invention

[0004] The object of the present invention is to provide an anti-ultraviolet thermal insulation film and a preparation method thereof, so as to solve the problems in the background technology.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A method for preparing an anti-ultraviolet thermal insulation film comprises the following steps:

[0007] Step S1, ultrasonically dispersing the M-phase vanadium dioxide-loaded carbon nanotubes in a copper sulfate pentahydrate aqueous solution, then adding a sodium thiosulfate aqueous solution, heating to 90° C. and stirring for reaction for 1 hour, filtering and retaining the filter residue, and drying the filter residue in an oven at 45° C. to obtain hybrid modified carbon nanotubes;

[0008] Step S2, ultrasonically disperse the hybrid modified carbon nanotubes and nano core-shell zinc oxide in deionized water, then add polyvinyl alcohol, stir and mix at 90-95°C for 2h to obtain a casting solution, and then use a coating applicator to scrape the casting solution on a glass plate, control the thickness of the wet film to be 1mm, and dry at 60°C for 12h to obtain an anti-ultraviolet thermal insulation film.

[0009] Furthermore, the usage ratio of the M-phase vanadium dioxide-loaded carbon nanotubes, copper sulfate pentahydrate aqueous solution and sodium thiosulfate aqueous solution is 0.3-0.5 g: 250 mL: 250 mL; the concentrations of the copper sulfate pentahydrate aqueous solution and the sodium thiosulfate aqueous solution are both 1 wt %.

[0010] Furthermore, the M-phase vanadium dioxide-loaded carbon nanotubes are prepared by the following steps:

[0011] Step A1, adding ammonium metavanadate into deionized water and stirring for 0.5-1h, after the ammonium metavanadate is completely dissolved, adding carbon nanotubes and stirring to mix evenly, then adding formic acid and reacting at 200°C for 48h, standing and cooling to room temperature, removing the supernatant, washing with 60°C deionized water and ethanol by alternating centrifugation for 3 times, and then drying in an oven at 60°C to obtain carbon nanotubes loaded with D-phase vanadium dioxide; using carbon nanotubes as carriers, loading D-phase crystalline vanadium dioxide on the carbon nanotubes through a hydrothermal reaction;

[0012] Step A2, loading the D-phase vanadium dioxide-loaded carbon nanotubes into a porcelain boat and placing it in a tube furnace, heating to 400°C at a heating rate of 5°C / min under nitrogen protection, annealing for 1 hour, and cooling to room temperature to obtain M-phase vanadium dioxide-loaded carbon nanotubes. By annealing at 400°C, the vanadium dioxide loaded on the carbon nanotubes is transformed from the D-phase crystal form to the M-phase crystal form.

[0013] Furthermore, the usage ratio of the ammonium metavanadate, deionized water, carbon nanotubes and formic acid is 7mmo l:80-100mL:0.1-0.15g:7mL.

[0014] Furthermore, the usage ratio of the hybrid modified carbon nanotubes, nano core-shell zinc oxide, deionized water and polyvinyl alcohol is 0.2-0.3g: 1-1.2g: 100mL: 15g. By controlling the mass ratio of the hybrid modified carbon nanotubes and nano core-shell zinc oxide to polyvinyl alcohol to 1.3-2% and 6.7-8%, the prepared thermal insulation film has better ultraviolet blocking performance and thermal insulation performance while ensuring visible light transmittance.

[0015] Furthermore, the nano core-shell zinc oxide is prepared by the following steps:

[0016] Zinc acetate dihydrate is added to anhydrous methanol and stirred to dissolve. After heating to 55-60° C., potassium hydroxide methanol solution is added. After high-speed stirring at 1000 r / min for reaction for 3-5 minutes, ethyl orthosilicate and ammonia solution are immediately added. The mixture is stirred at 500 r / min for reaction for 12 hours at 50° C., and then a silane coupling agent is added for ultrasonic dispersion for 1 hour. After centrifugal separation, washing and drying, nano core-shell zinc oxide is obtained.

[0017] Furthermore, the dosage ratio of the zinc acetate dihydrate, anhydrous methanol, potassium hydroxide methanol solution, tetraethyl orthosilicate, ammonia solution and silane coupling agent is 0.35-0.45g: 30-50mL: 1-3mL: 0.1-0.2g: 6-8mL: 0.5g; the concentration of the potassium hydroxide methanol solution is 1mol / L; the concentration of the ammonia solution is 1mol / L. Too little tetraethyl orthosilicate addition will result in the inability of the generated silicon dioxide to completely cover the nano zinc oxide particles, and the agglomeration of nano zinc oxide will still occur; too much tetraethyl orthosilicate addition will result in the nano zinc oxide particles being coated with too thick silicon dioxide, which will affect the transmittance of the nano core-shell zinc oxide to visible light.

[0018] Furthermore, the silane coupling agent is silane coupling agent A-172, and its chemical name is vinyl tri(β-methoxyethoxy) silane. As a surface modifier, the silane coupling agent is not only conducive to the dispersibility of nano-core-shell zinc oxide in deionized water, but also can improve the interface bonding force between nano-core-shell zinc oxide and polyvinyl alcohol, thereby improving the mechanical properties of the thermal insulation film.

[0019] Furthermore, the particle size of the nano core-shell zinc oxide is in the range of 1-10 nm. Compared with the existing method for preparing zinc oxide, the present invention uses nano zinc oxide particles as core and silicon dioxide as shell, and the obtained nano core-shell zinc oxide has a smaller particle size, better dispersibility, and better visible light transmittance.

[0020] An anti-ultraviolet heat-insulating film is prepared by the above preparation method.

[0021] Beneficial effects:

[0022] The present invention firstly loads M-phase vanadium dioxide tightly on the surface of carbon nanotubes through hydrothermal reaction and annealing treatment, and then loads copper sulfide which has strong absorption effect on near infrared rays, so as to obtain hybrid modified carbon nanotubes with multiple functions; on the one hand, carbon nanotubes themselves have extremely high tensile strength, and a small amount of addition can significantly improve the mechanical properties of the thermal insulation film, and after the hybrid modification of vanadium dioxide and copper sulfide, the roughness of the surface of carbon nanotubes is improved, and the interaction force between carbon nanotubes and polyvinyl alcohol is further improved, so that the thermal insulation film prepared by the present invention has more excellent tensile strength, thereby expanding the thermal insulation film of the present invention. The application scope of the film; on the other hand, carbon nanotubes have excellent heat conduction performance. When sunlight irradiates the thermal insulation film, copper sulfide first blocks most of the near-infrared rays through strong absorption and generates heat. The heat generated by copper sulfide is continuously accumulated and quickly transferred to M-phase vanadium dioxide through carbon nanotubes. When the temperature exceeds the phase transition temperature, M-phase vanadium dioxide is transformed into R-phase vanadium dioxide to reflect near-infrared rays, reducing the burden of copper sulfide. Copper sulfide, carbon nanotubes and M-phase vanadium dioxide synergistically respond quickly, significantly improving the insulation efficiency of the thermal insulation film to near-infrared rays, and further improving the thermal insulation performance of the thermal insulation film;

[0023] The invention prepares nano-core-shell zinc oxide by a precipitation method. Within 3-5 minutes of the rapid reaction of zinc acetate and potassium hydroxide, tetraethyl orthosilicate and an ammonia solution are immediately added. Silicon dioxide generated by hydrolysis interacts with nano-zinc oxide particles and gradually coats the surface of the nano-zinc oxide particles. This can effectively avoid the agglomeration of nano-zinc oxide particles to cause the size to increase, improve the dispersibility of the nano-zinc oxide particles and the contact area with sunlight, and the nano-core-shell zinc oxide formed after coating also has more excellent visible light transmittance and ultraviolet light blocking properties. It can also avoid direct contact between zinc oxide and polyvinyl alcohol, reduce the catalytic degradation effect of zinc oxide on polyvinyl alcohol, extend the service life of the thermal insulation film, reduce the thermal conductivity of the thermal insulation film to a certain extent, and further improve the thermal insulation performance of the thermal insulation film.

[0024] The present invention adds a small amount of hybrid modified carbon nanotubes and nano core-shell zinc oxide to polyvinyl alcohol, so that the prepared thermal insulation film can have excellent barrier properties against both ultraviolet rays and near-infrared rays, protect people from ultraviolet damage and produce significant thermal insulation effects, and has a wide application space; the preparation method of the present invention is simple, the raw material price is low, and the production cost can be effectively controlled to remain at a low level. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Example 1

[0027] This embodiment provides a carbon nanotube loaded with M-phase vanadium dioxide, which is prepared by the following steps:

[0028] Step A1, add 7 mmol ammonium metavanadate to 80 mL deionized water and stir for 0.5 h. After the ammonium metavanadate is completely dissolved, add 0.1 g carbon nanotubes and stir to mix evenly. Then add 7 mL formic acid and react at 200 ° C for 48 h. After standing and cooling to room temperature, remove the supernatant, wash with 60 ° C deionized water and ethanol alternately by centrifugation for 3 times, and then dry in an oven at 60 ° C to obtain D-phase vanadium dioxide-loaded carbon nanotubes;

[0029] Step A2, load the D-phase vanadium dioxide carbon nanotubes into a porcelain boat and place it in a tube furnace, heat it to 400°C at a heating rate of 5°C / min under nitrogen protection, anneal it for 1h, and cool it to room temperature to obtain the M-phase vanadium dioxide carbon nanotubes.

[0030] Example 2

[0031] This embodiment provides a carbon nanotube loaded with M-phase vanadium dioxide, which is prepared by the following steps:

[0032] Step A1, add 7 mmol ammonium metavanadate to 90 mL deionized water and stir for 1 h. After the ammonium metavanadate is completely dissolved, add 0.12 g carbon nanotubes and stir to mix evenly. Then add 7 mL formic acid and react at 200 ° C for 48 h. After standing and cooling to room temperature, remove the supernatant, wash with 60 ° C deionized water and ethanol alternately by centrifugation for 3 times, and then dry in an oven at 60 ° C to obtain D-phase vanadium dioxide-loaded carbon nanotubes;

[0033] Step A2, load the D-phase vanadium dioxide carbon nanotubes into a porcelain boat and place it in a tube furnace, heat it to 400°C at a heating rate of 5°C / min under nitrogen protection, anneal it for 1h, and cool it to room temperature to obtain the M-phase vanadium dioxide carbon nanotubes.

[0034] Example 3

[0035] This embodiment provides a carbon nanotube loaded with M-phase vanadium dioxide, which is prepared by the following steps:

[0036] Step A1, add 7 mmol ammonium metavanadate to 100 mL deionized water and stir for 1 h. After the ammonium metavanadate is completely dissolved, add 0.15 g carbon nanotubes and stir to mix evenly. Then add 7 mL formic acid and react at 200 ° C for 48 h. After standing and cooling to room temperature, remove the supernatant, wash with 60 ° C deionized water and ethanol alternately by centrifugation for 3 times, and then dry in an oven at 60 ° C to obtain D-phase vanadium dioxide-loaded carbon nanotubes;

[0037] Step A2, load the D-phase vanadium dioxide carbon nanotubes into a porcelain boat and place it in a tube furnace, heat it to 400°C at a heating rate of 5°C / min under nitrogen protection, anneal it for 1h, and cool it to room temperature to obtain the M-phase vanadium dioxide carbon nanotubes.

[0038] Comparative Example 1

[0039] The difference between this comparative example and Example 3 is that the operation of step A2 is not performed, and the remaining raw materials and steps are the same, thereby obtaining D-phase vanadium dioxide-loaded carbon nanotubes.

[0040] Comparative Example 2

[0041] This comparative example is different from Example 3 in that "0.15 g carbon nanotubes" are not added, and the remaining raw materials and steps are the same to obtain M-phase vanadium dioxide.

[0042] Example 4

[0043] This embodiment provides a nano-core-shell zinc oxide, which is prepared by the following steps:

[0044] 0.35 g of zinc acetate dihydrate was added to 30 mL of anhydrous methanol and stirred to dissolve. After heating to 55° C., 1 mL of potassium hydroxide methanol solution with a concentration of 1 mol / L was added. After high-speed stirring at 1000 r / min for 3 minutes, 0.1 g of tetraethyl orthosilicate and 6 mL of ammonia solution with a concentration of 1 mol / L were immediately added. The mixture was stirred at 500 r / min for 12 hours at 50° C., and then 0.5 g of silane coupling agent A-172 was added and ultrasonically dispersed for 1 hour. After centrifugal separation, washing and drying, nano-core-shell zinc oxide with a particle size range of 1-10 nm was obtained.

[0045] Example 5

[0046] This embodiment provides a nano-core-shell zinc oxide, which is prepared by the following steps:

[0047] 0.4 g of zinc acetate dihydrate was added to 40 mL of anhydrous methanol and stirred to dissolve. After heating to 60° C., 2 mL of potassium hydroxide methanol solution with a concentration of 1 mol / L was added. After high-speed stirring at 1000 r / min for 4 minutes, 0.15 g of tetraethyl orthosilicate and 7 mL of ammonia solution with a concentration of 1 mol / L were immediately added. The mixture was stirred at 500 r / min for 12 hours at 50° C., and then 0.5 g of silane coupling agent A-172 was added and ultrasonically dispersed for 1 hour. After centrifugal separation, washing and drying, nano-core-shell zinc oxide with a particle size range of 1-10 nm was obtained.

[0048] Example 6

[0049] This embodiment provides a nano-core-shell zinc oxide, which is prepared by the following steps:

[0050] 0.45 g of zinc acetate dihydrate was added to 50 mL of anhydrous methanol and stirred to dissolve. After heating to 60° C., 3 mL of potassium hydroxide methanol solution with a concentration of 1 mol / L was added. After stirring at a high speed of 1000 r / min for 5 minutes, 0.2 g of tetraethyl orthosilicate and 8 mL of ammonia solution with a concentration of 1 mol / L were immediately added. The mixture was stirred at 500 r / min for 12 hours at 50° C., and then 0.5 g of silane coupling agent A-172 was added and ultrasonically dispersed for 1 hour. After centrifugal separation, washing and drying, nano-core-shell zinc oxide with a particle size range of 1-10 nm was obtained.

[0051] Comparative Example 3

[0052] The difference between this comparative example and Example 6 is that the time of high-speed stirring reaction is extended from "5min" to "6min", and the other raw materials and steps are the same.

[0053] Comparative Example 4

[0054] This comparative example is compared with Example 6, except that "0.2 g of tetraethyl orthosilicate and 8 mL of 1 mol / L ammonia solution" are not added, and the remaining raw materials and steps are the same to obtain nano zinc oxide.

[0055] Comparative Example 5

[0056] This comparative example is compared with Example 6, except that "0.5 g of silane coupling agent A-172" is not added, and the other raw materials and steps are the same.

[0057] Example 7

[0058] This embodiment provides an anti-ultraviolet thermal insulation film, comprising the following steps:

[0059] Step S1, ultrasonically dispersing 0.3 g of the M-phase vanadium dioxide-loaded carbon nanotubes prepared in Example 1 in 250 mL of a 1 wt% aqueous solution of copper sulfate pentahydrate, then adding 250 mL of a 1 wt% aqueous solution of sodium thiosulfate, heating to 90° C. and stirring for 1 h, filtering and retaining the filter residue, and drying the filter residue in an oven at 45° C. to obtain hybrid modified carbon nanotubes;

[0060] Step S2, ultrasonically disperse 0.2 g of hybrid modified carbon nanotubes and 1 g of the nano core-shell zinc oxide prepared in Example 4 in 100 mL of deionized water, then add 15 g of polyvinyl alcohol, stir and mix at 90° C. for 2 h to obtain a casting solution, and then use a film applicator to scrape the casting solution on a glass plate, control the thickness of the wet film to be 1 mm, and dry at 60° C. for 12 h to obtain an anti-ultraviolet thermal insulation film.

[0061] Example 8

[0062] This embodiment provides an anti-ultraviolet thermal insulation film, comprising the following steps:

[0063] Step S1, ultrasonically dispersing 0.4 g of the M-phase vanadium dioxide-loaded carbon nanotubes prepared in Example 2 in 250 mL of a 1 wt% aqueous solution of copper sulfate pentahydrate, then adding 250 mL of a 1 wt% aqueous solution of sodium thiosulfate, heating to 90° C. and stirring for 1 h, filtering and retaining the filter residue, and drying the filter residue in an oven at 45° C. to obtain hybrid modified carbon nanotubes;

[0064] Step S2, ultrasonically disperse 0.25g of hybrid modified carbon nanotubes and 1.1g of the nano core-shell zinc oxide obtained in Example 5 in 100mL of deionized water, then add 15g of polyvinyl alcohol, stir and mix at 92°C for 2h to obtain a casting liquid, and then use a coater to scrape the casting liquid onto a glass plate, control the thickness of the wet film to be 1mm, and dry at 60°C for 12h to obtain an anti-ultraviolet thermal insulation film.

[0065] Example 9

[0066] This embodiment provides an anti-ultraviolet thermal insulation film, comprising the following steps:

[0067] Step S1, ultrasonically dispersing 0.5 g of the M-phase vanadium dioxide-loaded carbon nanotubes obtained in Example 3 in 250 mL of a 1 wt% aqueous solution of copper sulfate pentahydrate, then adding 250 mL of a 1 wt% aqueous solution of sodium thiosulfate, heating to 90° C. and stirring for 1 h, filtering and retaining the filter residue, and drying the filter residue in an oven at 45° C. to obtain hybrid modified carbon nanotubes;

[0068] Step S2, ultrasonically disperse 0.3 g of hybrid modified carbon nanotubes and 1.2 g of the nano core-shell zinc oxide obtained in Example 6 in 100 mL of deionized water, then add 15 g of polyvinyl alcohol, stir and mix at 95 ° C for 2 h to obtain a casting liquid, and then use a coater to scrape the casting liquid on a glass plate, control the thickness of the wet film to be 1 mm, and dry at 60 ° C for 12 h to obtain an anti-ultraviolet thermal insulation film.

[0069] Comparative Example 6

[0070] Compared with Example 9, the difference between this comparative example is that in step S1, the "M-phase vanadium dioxide-loaded carbon nanotubes prepared in Example 3" are replaced by an equal amount of "D-phase vanadium dioxide-loaded carbon nanotubes prepared in Comparative Example 1", and the other raw materials and steps are the same.

[0071] Comparative Example 7

[0072] The difference between this comparative example and Example 9 is that in step S1, the "M-phase vanadium dioxide-loaded carbon nanotubes prepared in Example 3" is replaced by an equal amount of "M-phase vanadium dioxide prepared in Comparative Example 2", and the other raw materials and steps are the same.

[0073] Comparative Example 8

[0074] Compared with Example 9, the difference between this comparative example is that in step S2, the "nano core-shell zinc oxide prepared in Example 6" is replaced by an equal amount of "nano core-shell zinc oxide prepared in Comparative Example 3", and the other raw materials and steps are the same.

[0075] Comparative Example 9

[0076] Compared with Example 9, this comparative example differs in that in step S2, the "nano core-shell zinc oxide prepared in Example 6" is replaced by an equal amount of "nano zinc oxide prepared in Comparative Example 4", and the remaining raw materials and steps are the same.

[0077] Comparative Example 10

[0078] Compared with Example 9, this comparative example differs in that in step S2, the "nano core-shell zinc oxide prepared in Example 6" is replaced by an equal amount of "nano core-shell zinc oxide prepared in Comparative Example 5", and the other raw materials and steps are the same.

[0079] The performance tests were conducted on the thermal insulation films prepared in Examples 7 to 9 and Comparative Examples 6 to 10. According to GB / T1040-2006 standard, the tensile strength and elongation at break of the samples were tested using a universal tensile testing machine. The transmittance of the thermal insulation films in the range of 250-2500nm for ultraviolet light, visible light and near infrared light was tested using a UV / VIS / NIR spectrophotometer. The thermal insulation film samples were installed at the top opening of the thermal insulation box, the probe of the electronic thermometer was located inside the thermal insulation box, and the power was 0.6W / cm2 The simulated sunlight was used as the light source, irradiated at room temperature for 300s, and the temperature in the incubator was recorded. The results are shown in Table 1:

[0080] Table 1

[0081]

[0082] It can be seen from the data in Table 1 that the thermal insulation films prepared in Examples 7 to 9 have more excellent mechanical properties, optical properties and thermal insulation properties; compared with Comparative Examples 6 and 7, the present invention successively loads M-phase vanadium dioxide and copper sulfide on carbon nanotubes, and the three act synergistically to make the prepared hybrid modified carbon nanotubes evenly dispersed in the thermal insulation film, which can significantly improve the mechanical tensile properties and near-infrared blocking properties of the thermal insulation film, thereby achieving excellent thermal insulation effect; compared with Comparative Examples 8 to 10, the nano core-shell zinc oxide prepared in the present invention has the advantages of smaller particle size, good dispersibility and high visible light transmittance, and can significantly improve the ultraviolet blocking performance of the thermal insulation film.

[0083] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0084] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing an anti-ultraviolet thermal insulation film, characterized in that: The following steps are involved: Step S1, ultrasonically dispersing the M-phase vanadium dioxide-loaded carbon nanotubes in a copper sulfate pentahydrate aqueous solution, then adding a sodium thiosulfate aqueous solution, heating to 90° C. and stirring for reaction for 1 hour, filtering and drying to obtain hybrid modified carbon nanotubes; Step S2, ultrasonically dispersing the hybrid modified carbon nanotubes and nano core-shell zinc oxide in deionized water, then adding polyvinyl alcohol, stirring and mixing at 90-95° C. for 2 hours to obtain a casting solution, then scraping the casting solution on a glass plate, and after drying, obtaining an anti-ultraviolet thermal insulation film.

2. The method for preparing an anti-ultraviolet thermal insulation film according to claim 1, characterized in that: The usage ratio of the M-phase vanadium dioxide-loaded carbon nanotubes, copper sulfate pentahydrate aqueous solution and sodium thiosulfate aqueous solution is 0.3-0.5 g: 250 mL: 250 mL; the concentrations of the copper sulfate pentahydrate aqueous solution and the sodium thiosulfate aqueous solution are both 1 wt %.

3. The method for preparing an anti-ultraviolet thermal insulation film according to claim 1, characterized in that: The M-phase vanadium dioxide-loaded carbon nanotubes are prepared by the following steps: Step A1, adding ammonium metavanadate into deionized water and stirring to dissolve, adding carbon nanotubes and stirring to mix evenly, then adding formic acid and reacting at 200° C. for 48 hours, standing and cooling to room temperature, removing the supernatant, centrifuging, washing, and drying to obtain D-phase vanadium dioxide-loaded carbon nanotubes; Step A2, transfer the D-phase vanadium dioxide-loaded carbon nanotubes into a tubular furnace, heat to 400°C at a heating rate of 5°C / min under nitrogen protection, anneal for 1 hour, and cool to room temperature to obtain M-phase vanadium dioxide-loaded carbon nanotubes.

4. The method for preparing an anti-ultraviolet thermal insulation film according to claim 3, characterized in that: The usage ratio of the ammonium metavanadate, deionized water, carbon nanotubes and formic acid is 7 mmol: 80-100 mL: 0.1-0.15 g: 7 mL.

5. The method for preparing an anti-ultraviolet thermal insulation film according to claim 1, characterized in that: The usage ratio of the hybrid modified carbon nanotube, nano core-shell zinc oxide, deionized water and polyvinyl alcohol is 0.2-0.3 g: 1-1.2 g: 100 mL: 15 g.

6. The method for preparing an anti-ultraviolet thermal insulation film according to claim 1, characterized in that: The nano core-shell zinc oxide is prepared by the following steps: Zinc acetate dihydrate is added to anhydrous methanol and stirred to dissolve. After heating to 55-60°C, potassium hydroxide methanol solution is added. After stirring and reacting for 3-5 minutes, ethyl orthosilicate and ammonia solution are immediately added. The mixture is stirred and reacted at 50°C for 12 hours. Then, a silane coupling agent is added and ultrasonically dispersed for 1 hour. The mixture is centrifuged, washed, and dried to obtain nano core-shell zinc oxide.

7. The method for preparing an anti-ultraviolet thermal insulation film according to claim 6, characterized in that: The dosage ratio of the zinc acetate dihydrate, anhydrous methanol, potassium hydroxide methanol solution, tetraethyl orthosilicate, ammonia solution and silane coupling agent is 0.35-0.45g:30-50mL:1-3mL:0.1-0.2g:6-8mL:0.5g; the concentrations of the potassium hydroxide methanol solution and ammonia solution are both 1mol / L.

8. The method for preparing an anti-ultraviolet thermal insulation film according to claim 6, characterized in that: The silane coupling agent is silane coupling agent A-172.

9. The method for preparing an anti-ultraviolet thermal insulation film according to claim 1, characterized in that: The particle size of the nano core-shell zinc oxide is in the range of 1-10 nm.

10. An anti-ultraviolet thermal insulation film, characterized in that: Prepared by the preparation method according to any one of claims 1 to 9.